ANALISIS REAKSI PASAR MODAL INDONESIA TERHADAP PENGUMUMAN MAKING INDONESIA 4.0 (EVENT STUDY PADA LIMA SUB SEKTOR PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Marcellina Nadia Christy ; Putu Prima Wulandari, MSA,. Ak
The aim of this study is to explore the reactions of the Indonesian capital market to the announcement of Making Indonesia 4.0. This study used the event study method, wherein observations were made on the average of abnormal returns and trading volume activity with an event window of 21 days. The population of this study is 61 manufacturing companies engaged in the food and drink, textile and garment, automotive, chemistry, and electronics subsectors and are listed in Indonesia Stock Exchange up to 2018. Using the purposive sampling method, 45 companies were chosen as the research sample. The results of the study, obtained through the parametric test and paired samples test, showed that there was no significant difference in abnormal returns and trading volume activity before and after the announcement with significance values of 0.738 and 0.051 respectively, which are larger than the significance level of 0.05. There was no significant difference in abnormal returns and trading volume activity before and after the announcement of Making Indonesia 4.0 because 1) the announcement of Making Indonesia 4.0 has no information content for investors that can affect investment decisions in the capital market, and 2) investors still wait and see in the stock exchange for the long-term implementation of the Making Indonesia 4.0 strategy in terms of increasing the production capacity of a company, assets, or profits. _x000D_ _x000D_ _x000D_ Keywords: Making Indonesia 4.0, Industry 4.0, information technology investment, abnormal returns, trading volume activity